PSYCHOLOGICAL CHARACTERISTICS OF FEELINGS DISTANCE IN BOXERS - Ishtaev Javlon Mavlonboevich; Mirjamolov Mekhriddin Kxayriddinovich; Rakxmanov Eldor Tolibjonovich; Norqobilov Muxiddin Najimovich (Proximus Journal Publishing, 2024)
In this article, the author tried to shed light on the psychological features of feeling the gap in boxers through a new methodology. The author tried to explain the elements of feeling of distance in boxers using a device that allows measuring nine types of distance in boxers.
Keywords: boxer; interval; distance